Gender Incidence in the Salary of Informal Workers for the Management of Socioeconomic Strategies - E. Melendres Medina; M. Campaña Lara; B. Riera Riera; J. Orozco Carrillo (ESPOCH Congresses)
This research examined the problems experienced by women who work in the informal sector of the city of Riobamba due to receiving poor and lower incomes than men. The main objective was to analyze the influence that gender has on wages of women in this sector, to establish strategies that can promote more equitable development. Qualitative and quantitative approaches were used using inductive and deductive methods. Data were collected through a survey and analyzed using the Chi square test. The results showed that women's wages were dependent on their gender, conditioned by a sociocultural environment that has not evolved, especially in the informal sectors made up mostly of rural population. Also, the presence of child labor was evident, and wages could not cover the basic needs of women who identified as heads of household with family responsibilities of between three to five people. The strategy identified to promote equity in the recognition and value of fair work without distinction of gender was based on the following elements: the implementation of inclusion policies and control, training of young women in non-traditional trades, promotion of changes in traditional patterns in households, and policies to combat poverty with a gender focus for sustainable social development.